Enhancing Science Learning in Grade III: a Classroom Action Research on the Impact of Demonstrative Teaching Methods in Exploring Properties of Matter - Nurmawati Nurmawati; Asnita Hasibuan; Rosdiana Samosir (Journal on Education, 2024)
This research intends to analyze the impact of introducing the display method in natural science (science) learning for grade III students in an elementary school. The demonstrative technique is used as a strategy to strengthen students' grasp of the subject matter, notably the qualities of objects. The research was conducted through a classroom action research approach with two cycles. The research results reveal a considerable boost in student learning outcomes along with the deployment of the demonstration approach. From the pre-cycle which attained 38% classical learning completeness, this level grew to 90.5% in cycle II. These data give proof that the demonstration technique has a positive impact on students' achievement of learning mastery. In addition, the favorable response from teachers and students to the presentation technique shows that it is not only helpful in reaching academic goals, but also produces a joyful and fascinating learning experience. Student involvement in direct observation, filling in observation tables, and group discussions suggests student interest for this method.